Dinamika Konflik Suami - Istri Pada Masa Awal Perkawinan - Grace Kilis (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2014)
This qualitative research aimed to describe the dynamic of marital conflict and conflict resolution in early stage ofmarriage. There are four participants (two couples) who are in theirfirst year of marriage. The results showed that marital conflict in early stage of marriage developed in several areas : relation with family of origin, financial management, work, daily habits, love and sexual expression, social and recreational activity, and relation with friends. Conflict resolution type that effective in solving problems in all areas is collaboration type. Factors that causing marital conflict are personality characteristic, difference in value and way of life, discrepancy between expectancy and reality, and inadequate communication skills. Effect of marital conflict is related to the conflict resolution type. Conflict resolution type with solution that satisfied both parties will improve the quality ofmarriage, and vice versa. Keywords : marital conflict, conflict resolution, early stage of marriage